2017
DOI: 10.1080/16512235.2017.1322447
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial diversity in health and disease: experience of healthy Indian subjects, and colon carcinoma and inflammatory bowel disease patients

Abstract: Background: The intestinal microbiota, through complex interactions with the gut mucosa, play a key role in the pathogenesis of colon carcinoma and inflammatory bowel disease (IBD). The disease condition and dietary habits both influence gut microbial diversity. Objective: The aim of this study was to assess the gut microbial profile of healthy subjects and patients with colon carcinoma and IBD. Healthy subjects included ‘Indian vegetarians/lactovegetarians’, who eat plant produce, milk and milk products, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 41 publications
7
43
1
1
Order By: Relevance
“…Similar conclusions has been reached also for obese people (44,45). Reduction in the proportion of Bacteroidetes with respect to Firmicutes was observed also in patients affected by inflammatory bowel disease in comparison to healthy controls (46)(47)(48). A more significant effect on the Bacteroidetes/Firmicutes ratio was demonstrated in patients with colon cancer, where the Firmicutes genera strongly dominated (47).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar conclusions has been reached also for obese people (44,45). Reduction in the proportion of Bacteroidetes with respect to Firmicutes was observed also in patients affected by inflammatory bowel disease in comparison to healthy controls (46)(47)(48). A more significant effect on the Bacteroidetes/Firmicutes ratio was demonstrated in patients with colon cancer, where the Firmicutes genera strongly dominated (47).…”
Section: Discussionsupporting
confidence: 80%
“…Reduction in the proportion of Bacteroidetes with respect to Firmicutes was observed also in patients affected by inflammatory bowel disease in comparison to healthy controls (46)(47)(48). A more significant effect on the Bacteroidetes/Firmicutes ratio was demonstrated in patients with colon cancer, where the Firmicutes genera strongly dominated (47). A similar shift in the Bacteroidetes/Firmicutes ratio has been demonstrated also for children suffering with autism spectrum disorder (49) and people under chronic stress (50).…”
Section: Discussionsupporting
confidence: 59%
“…The width of the connecting lines is proportional to the absolute value of the correlation coefficient. (2020) 10:5450 | https://doi.org/10.1038/s41598-020-62224-3 www.nature.com/scientificreports www.nature.com/scientificreports/ other diseases such as obesity and inflammatory bowel disease [24][25][26] . The decrease in the gut microbe diversity of T2D patients could induce a certain degree of gut bacterial dysbiosis and interfere with the interaction between gut microbiota and hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria, including Lactobacillus and Bifidobacterium , are probiotics that colonize the intestine. A healthy intestinal floral composition is characterized by a larger number of probiotic bacteria and a lower number of coliforms (Bamola et al, ). Our study demonstrated that feeding quails with supplementary doses of AMSL could significantly improve the composition of the gut microbiota by reducing the quantity of coliforms and increasing lactic acid bacteria, especially with the addition of 3%–5% concentrations of AMSL.…”
Section: Discussionmentioning
confidence: 99%